Exploration of New Drug Candidate Derived from Antioxidants of Korean Native Halophytes: Control of Acinetobacter baumannii with Antipathogenic Activity - Jihee Lee; Ho Sung Kim; Jeong Woo Park; Bohyun Yun; Woo Young Bang; Ki Hwan Moon; Youngwan Seo (Antioxidants)
The rise of antibiotic-resistant bacteria poses a significant challenge to the treatment of bacterial infections, necessitating the development of novel antibiotics or strategies to preserve the efficacy of existing ones. This study investigates the role of oxidative stress modulation in the pathogenicity of multidrug-resistant (MDR) bacterial strains, aiming to identify potential avenues for new drug design. Specifically, the anti-biofilm effects of crude extracts and fractions from seven halophyte species native to Jeju Island, South Korea, were evaluated against Acinetobacter baumannii ATCC 17978. Notably, the 85% aqueous methanol fraction of Peucedanum japonicum Thunb. (Pj) and the n-hexane fraction of Lysimachia mauritiana Lam. (Lm) demonstrated significant anti-biofilm activity. Further assessments revealed that these fractions also exhibited notable antioxidant and anti-inflammatory properties, with the Pj fraction showing a lifespan extension effect in the Caenorhabditis elegans model. These findings suggest that Pj and Lm hold promise as potential candidates for the development of new therapeutic agents targeting MDR bacteria.